PENYALURAN DARI TUNAI KE NON TUNAI: STUDI PERAN PENDAMPING DALAM MENGAWAL KONVERSI PKH DI DLINGO - Riswantoro, Riswantoro (Universitas Islam Negeri Sunan Kalijaga, 2018)
Conditional Cash Transfer (CCT) is the country’s poverty reduction policy. In 2017, CCT has changed its cash distribution mechanism to non-cash. The change in the distribution mechanism was alleged as the state’s response to the problems that arose beforehand so that through non-cash it could be really well received by the beneficiaries effectively. This policy change is evenly distributed throughout Indonesia, including in Bantul Regency, Dlingo District. To see the effectiveness of the program from cash to non-cash, this article aims to examine the role of facilitators in the distribution process to beneficiaries. This article is a development of the results of qualitative research. The data collection is through the interview, observation, and documentation methods. Meanwhile, not all participants were interviewed, but only a small part was taken by probability sampling methods. The results of the study in this article show that the role of the facilitator can run effectively with several main activities, including participant sharing, education, and training for beneficiaries, assisting the priority and empowering potential, and organizing learning groups.[Program Keluarga Harapan (PKH) adalah kebijakan penanggulangan kemiskinan negeri ini. Di tahun 2017 PKH telah berubah mekanisme penyalurannya dari tunai menjadi non tunai. Perubahan mekanisme penyaluran ini disinyalir sebagai respon negara atas persoalan yang muncul sebelumnya sehingga melalui non tunai dapat betul-betul diterima dengan baik oleh Keluarga Penerima Manfaat (KPM) secara efektif. Perubahan kebijakan ini merata di seluruh Indonesia tidak terkecuali di Kabupaten Bantul, Kecamatan Dlingo. Untuk melihat efektivitas program dari tunai ke non tunai, artikel ini hendak mengkaji tentang peran pendamping dalam proses penyaluran kepada KPM. Artikel ini merupakan pengembangan dari hasil penelitian kualitatif. Adapun pengambilan data melalui metode wawancara, observasi, dan dokumentasi. Tentu pengambilan data tidak semua peserta diwawancarai, namun hanya sebagian kecil diambil dengan metode probability sampling. Hasil kajian pada artikel ini menunjukan bahwa peran pendamping dapat berjalan secara efektif dengan beberapa kegiatan pokok, antara lain: pembagian peserta, pendidikan dan pelatihan bagi KPM, mendampingi yang prioritas dan memberdayakan yang potensial, dan pengorganisasian kelompok belajar.]